The Comparison of Maladaptive Schema and Lifestyles in Drug Dependence and Non-Drug Dependence People - Vahideh Purmohammad; Hasan Yaghoubi; Rahim Yousefi; Ali Mohammadzadeh; Mahmod Najafi (Drug Control Headquarters, Research and Education Office, 2013)
Objective: The aim of this study was to compare early maladaptive schemas and life styles in drug dependences and normal population to recognize their role in drug dependence. Due to their importance in interpretation of special situations, cognitive schemas and life styles have a significant role in cognitive theories. Methods: The method of this research were post-facto and sectional styles. The population were included of 100 drug dependence adults and 100 non-drug dependence who were selected by at-reach methods. Young early maladaptive schema-short form and Basic Adlerian scales for interpersonal success-adult form questionnaires were used. Findings: the results showed that there were significant differences between early maladaptive schemas and life styles in groups under research. Conclusion: the study showed that drug dependence people suffer from high levels of early maladaptive schemas and their life styles are maladaptive. As a result, in prediction of dependence to drug and in treating it too much attention must be given to cognitive factors.